Zbrojenia Japonii w obliczu napiętej sytuacji w Azji Wschodniej - Michał Iwańczuk (Przegląd Geopolityczny)
The following paper attempts to answer the question of why Japan, after many years of pursuing a pacifist foreign policy, starting from the end of World War II, has decided to significantly strengthen its military capabilities. The author analyzes the geopolitical factors affecting Japan's security, the international situation in the region, potential threats to the state, as well as the current capabilities of Japan's Self-Defense Forces and key plans for their expansion, such as the acquisition of missiles that enable counter-strikes, the development of air defense and investment in modern military technology. Also discussed are key historical aspects in the development of Japan's armed forces and legal solutions directly affecting the capabilities of the Self-Defense Forces.